Exploring the involvement of the alternative complement pathway in non-infectious uveitis pathogenesis - Kulshrestha, Prerna; Goel, Pallavi; Murthy, Somasheila; Tyagi, Mudit; Basu, Soumvaya; Gogri, Pratik; Kaur, Inderjeet (Frontiers in Immunology, 2023)
Purpose: Non-infectious uveitis is a complex disease characterized by intraocular inflammation of the uveal area and leading cause of vision impairment and blindness in the young generation of people worldwide.However, what triggers inflammation and contributes to its recurrence remains unclear. The complement system has been linked to various immunological and inflammatory conditions. In the present study, we have systematically evaluated the role of the alternate complement pathway in the pathogenesis of non-infectious uveitis.Quantitative PCR was done in the peripheral leukocytes for studying the expression of genes and regulatory miRNA in both anterior and posterior uveitis (n=28 in each category). Multiplex ELISA was performed to measure the alternate pathway complement components like C3b, factor B and CFH and aqueous humor of infectious, non-infectious uveitis patients and non-inflammatory controls (n=10 each). Western blotting was done to validate the ELISA findings in a subset of patients and controls.Results Down-regulation of C3 and CFH mRNA in the peripheral blood was shown by Q-PCR in the group of anterior uveitis, while opposite result was found in the group of posterior uveitis. ELISA levels of C3b and CFH proteins were significantly higher in aqueous humor of infectious and non-infectious uveitis (*p = 0.03 and **p = 0.0007 respectively) as compared to control. Western blotting further validated the activation of complement cascade in the aqueous and vitreous humor of non-infectious uveitis patients with an increased level of C3b (n=6) and CFH (n=4) in aqueous humor. C3b level was significantly increased while CFH was reduced relative to controls in the vitreous humor of posterior uveitis patients compared to controls (n=27 in each category). A C3b to CFH ratio was computed to assess the regulation of complement activation and this index was several folds higher in both anterior and posterior uveitis (n=10 each). The expression of miRNA-146 and miRNA-155 that regulate CFH was downregulated and nicely correlated with the increased complement proteins in both anterior and posterior uveitis (n=10 each).Our results clearly demonstrate a clear role of CFH and the activation of alternate complement pathway in the pathogenesis of non-infectious uveitis however its therapeutic potential warrants further investigations.